2017
DOI: 10.1002/jcop.21845
|View full text |Cite
|
Sign up to set email alerts
|

The Community Culture Survey: Preliminary Findings From a New Approach to Measurement and Understanding Health Disparities

Abstract: The Community Culture Survey (CCS) was designed to advance the measurement of culture and its link to health by asking individuals to describe the attitudes and behaviors of people in the local community where they live.  To assess preliminary validity, 130 respondents completed the CCS, a health survey, and demographic questions.  Five subscales were derived from the CCS, 2 of which were correlated with health survey items.  Residents living in neighborhoods described as higher in Social Responsibility and Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A key challenge to progress in this research is the measurement of culture ( Farmer et al, 2012 Oct , Gessert et al, 2015 ). While preliminary results indicate that dimensions of community culture predict health status, more research is needed to determine if and how these relationships differentially impact health and mortality in rural versus urban settings ( Pellegrin & Nigg, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A key challenge to progress in this research is the measurement of culture ( Farmer et al, 2012 Oct , Gessert et al, 2015 ). While preliminary results indicate that dimensions of community culture predict health status, more research is needed to determine if and how these relationships differentially impact health and mortality in rural versus urban settings ( Pellegrin & Nigg, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, community norms and functioning are recognized as key factors related to health and disparities. Reflecting these domains, the Community Culture Survey (CCS) conceptually defines community culture as “a shared way of life reflected in consistent patterns of values, attitudes, and behaviors” that are meaningful to people who live in a local community or neighborhood and that distinguishes one local community/neighborhood from another [ 13 ]. In contrast to measures that aggregate individuals’ values, attitudes and behaviors, the CCS asks participants to describe their neighborhood community norms irrespective of their own values, attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data from research conducted in Hawaiʻi, one of the most racially/ethnically diverse states in the US, indicated that dimensions of the original 42-item Community Culture Survey (CCS) may be helpful in understanding cultural determinants of health [ 13 ]. However, the small sample size and uniqueness of Hawaiʻi limit the generalizability of findings from the pilot study to broader contexts.…”
Section: Introductionmentioning
confidence: 99%